(untitled) (Research, Society and Development, 2024)
Antinutritional compounds are produced by the secondary metabolism of plants and have several functions, including protecting against predator attacks. These substances can reduce the bioavailability of nutrients, affect the digestibility of proteins, as well as cause toxic effects to the body when consumed in excess. However, in addition to harmful effects, some of these phytochemicals may also have beneficial effects on human health. This review aims to present data on the presence and content of antinutrients in vegetables and also report functional effects of some of these compounds. The present work is an integrative review, in which a search was carried out in the electronic databases Science Direct, Google Scholar and the Integrated Search Portal of the University of São Paulo, bringing together articles that addressed the concentration of antinutritional compounds in plant foods. used in human nutrition. The most abundant antinutrients in the foods evaluated were phytates, followed by tannins, oxalates, saponins, protease inhibitors (including trypsin inhibitors), nitrates, cyanogenic glycosides, non-digestible carbohydrates (raffinose, stachyose and verbascose) and glucosinolates. This review presented important data on the presence and content of antinutritional compounds in fresh and processed vegetables, highlighting the occurrence of phytates, tannins and oxalates. Research has shown harmful effects and also beneficial actions of the compounds, however, the potential of these molecules still needs to be investigated to elucidate their beneficial effects on human health and their applications.